Hubungan antara Adversity Intelligence dengan Work-Family Conflict pada Guru Wanita di Sekolah Kalam Kudus Mayang Medan - Elvina Elvina; Winida Marpaung; Yulinda S. Manurung (Psyche 165 Journal, 2021)
This study aims to determine the reIationship between Adversity Intelligence with Work Family Conflict. The research subject used in this study wer 90 female teachers at the Kalam Kudus School. Data obtained from a scale to measure Adversity Intelligence and Work FamiIy ConfIict. Analys of the data use is using Pearson Product Moment CorreIation. The results of data analysis showed a correlation coefficient of -0.715 (p <0.05) and showed a negative relationship between Adversity Intelligence Work FamiIy ConfIict. The results of this study indicate that the contribution of Adversity Intelligence to Work FamiIy ConfIict is 51.1 percent, this indicates a very significant reIationship between the variabIe Adversity Intelligence with Work FamiIy ConfIict on teachers